“I feel as though I would not be able to empathize”: Intersectionality and Counselor Intergroup Anxiety - Krista M Malott; Edward Wahesh; Tina Paone; Amber S Haley; Alexis McClatchy (Teaching and Supervision in Counseling, 2025)
Researchers applied a thematic analysis in this study to examine the nature of master-level counseling students’ (N = 19) intergroup anxiety (IA), a form of bias characterized by an anxious response to others based on negative views of that person’s identity (Stephan, 2014). Students cited stronger IA reactions toward persons with multiple identity traits (i.e., intersectionality). Traits chosen varied widely, some being dominant (e.g., White, male, able-bodied), and others, minoritized in nature (e.g., Black, Muslim, disabled). Thematic explanations for IA reactions varied, including a fear of client judgement, prior negative experiences with persons of certain traits, limited knowledge of clients’ experiences, and opposing views from certain clients. Participants expressed doubt that they would be able to connect with, or feel empathy for, clients of named intersectional traits. Findings suggest the salience of intersectionality and the importance of providing a more complex, nuanced, open, and adaptive curriculum and supervisory experience to meet students’ learning needs.
Keywords: intersectionality; counseling; intergroup anxiety; empathy; bias